2004
DOI: 10.1074/jbc.m308999200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SOCS-3 Promoter Responses to Interferon γ

Abstract: SOCS-3 (suppressor of cytokine signaling 3) is an intracellular protein that is selectively and rapidly induced by appropriate agonists and that modulates responses of immune cells to cytokines by interfering with the Janus kinase/signal transducer and activator of transcription (Jak/STAT) pathway. On the basis of the observations that interferon ␥ (IFN␥) up-regulates SOCS-3 gene and protein expression in primary mouse macrophages, J774 macrophage cell line and embryonal fibroblasts, we investigated which sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…Recent studies have demonstrated that Socs3 gene expression can be stimulated by a STAT1-dependent pathway in response to IFNγ (54). Moreover, STAT1 and STAT3 were found to have interchangeable functions in IFNγ-dependent regulation of SOCS3 (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that Socs3 gene expression can be stimulated by a STAT1-dependent pathway in response to IFNγ (54). Moreover, STAT1 and STAT3 were found to have interchangeable functions in IFNγ-dependent regulation of SOCS3 (57).…”
Section: Discussionmentioning
confidence: 99%
“…Suppressor of cytokine signaling (SOCS)-3 is induced rapidly by activated STATs via the presence of a STAT binding element in its promoter (34,35). To investigate the role of PDTC on the expression of SOCS3 protein, HepG2 cells were treated with the drug for 2 h before the addition of IL-6 for 90 min, and protein lysates were subjected to immunoblot analysis.…”
Section: Il-6-mediated Gene Expression Is Sensitive To Pdtc In Hepg2mentioning
confidence: 99%
“…Now that we have established the PI3K/AKT pathway to be critical for the up-regulation of SOCS3, we tried to find out the transcription factor involved in this pathway. The Socs-3 promoter contains numerous potential regulatory elements (45,46). A careful analysis of its promoter sites revealed two potential binding sites for KLF4 and multiple binding sites for AP-1 and NF-B.…”
Section: Discussionmentioning
confidence: 99%